Molecular chaperone TRiC governs avian reovirus replication by protecting outer-capsid protein σC and inner core protein σA and non-structural protein σNS from ubiquitin- proteasome degradation - Huang, Wei-Ru; Li, Jyun-Yi; Liao, Tsai-Ling; Yeh, Chuan-Ming; Wang, Chi-Young; Wen, Hsiao-Wei; Hu, Nien-Jen; Wu, Yi-Ying; Hsu, Chao-Yu; Chang, Yu-Kang; Chang, Ching-Dong; Nielsen, Brent L.; et al. (Veterinary microbiology, 2022)
•TRiC stabilizes the outer-capsid protein σC, inner core protein σA, and the non-structural protein σNS of ARV.•TriC serves as a chaperone of viral proteins and prevents their degradation via the ubiquitin-proteasome pathway.•Inhibition of TRiC significantly reduced expression levels of σC, σA, and σNS proteins of ARV and virus yield. Avian reoviruses (ARVs) are important pathogens that cause considerable economic losses in poultry farming. To date, host factors that control stabilization of ARV proteins remain largely unknown. In this work we determined that the eukaryotic chaperonin T-complex protein-1 (TCP-1) ring complex (TRiC) is essential for avian reovirus (ARV) replication by stabilizing outer-capsid protein σC, inner core protein σA, and the non-structural protein σNS of ARV. TriC serves as a chaperone of viral proteins and prevent their degradation via the ubiquitin-proteasome pathway. Furthermore, reciprocal co-immunoprecipitation assays confirmed the association of viral proteins (σA, σC, and σNS) with TRiC. Immunofluorescence staining indicated that the TRiC chaperonins (CCT2 and CCT5) are colocalized with viral proteins σC, σA, and σNS of ARV. In this study, inhibition of TRiC chaperonins (CCT2 and CCT5) by the inhibitor HSF1A or shRNAs significantly reduced expression levels of the σC, σA, and σNS proteins of ARV as well as virus yield, suggesting that the TRiC complex functions in stabilization of viral proteins and virus replication. This study provides novel insights into TRiC chaperonin governing virus replication via stabilization of outer-capsid protein σC, inner core protein σA, and the non-structural protein σNS of ARV.